Critical success factor that contributes towards successful migration to grid computing / Hazami Hussin - Hussin, Hazami (2013)
Grid Computing have been developed and deployed many years in the past and still continuous research been made to improve knowledge and its‘ result. Many are looking at Grid Computing as a potential solution to large network environment. This research focused on three (3) potential critical success factors for an organization towards migrating to Grid Computing; business factors, technical factors and organizational factors. The main adopted research method in this study has been quantitative research and evaluation based on case study at a higher institution education. The conclusion and recommendation also been discussed in the last chapter.